2017
DOI: 10.2147/ott.s142587
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and efficacy of chronic myeloid leukemia onset with extreme thrombocytosis in the era of tyrosine kinase inhibitors

Abstract: The aim of this study was to investigate the clinical characteristics and efficacy of chronic myeloid leukemia (CML) onset with extreme thrombocytosis. A total of 121 newly diagnosed and untreated CML patients in chronic phase with complete clinical information from the First Hospital of Jilin University, from January 2010 to December 2014 were retrospectively recruited. Based on the platelet (PLT) count, 22 patients were assigned into CML with thrombocytosis (CML-T) group (PLT >1,000×109/L) and 65 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Patients with CML are, in many cases, asymptomatic at diagnosis and only incidentally detected upon abnormalities found on routine blood testing. CML is the most common condition in the spectrum of MPDs [3]. It typically presents with leukocytosis, with elevated immature granulocytes, basophilia, and eosinophilia in the PB [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with CML are, in many cases, asymptomatic at diagnosis and only incidentally detected upon abnormalities found on routine blood testing. CML is the most common condition in the spectrum of MPDs [3]. It typically presents with leukocytosis, with elevated immature granulocytes, basophilia, and eosinophilia in the PB [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…CML is the most common condition in the spectrum of MPDs [3]. It typically presents with leukocytosis, with elevated immature granulocytes, basophilia, and eosinophilia in the PB [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally reported that thrombocytosis in adult CML patients has no close relationship with haemorrhagic and thrombotic events. When single centre studies investigated the episodes of haemorrhagic and thrombotic events, 22 out of 85 (26%) adult Chinese CML patients were assigned into CML with thrombocytosis but only one patient was detected with thrombosis at diagnosis, and no case with bleeding was observed (Liu et al , ). In an analysis from a single Italian centre, only one out of 100 adult CML patients developed thrombosis at diagnosis, and no history of bleeding was reported (Sorà et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…This proportion observed is in the range of haemostatic complications (10Á3%) reported for adults with CML at diagnosis. But it must be stressed that the data for adult cohorts usually comprise the sum of thrombotic and haemorrhagic complications (Schafer, 1984;Liu et al, 2017;Sora et al, 2018) while no case of thrombosis was observed in childhood CML although the proportion of patients exhibiting a platelet count >1 000 9 10 9 /l was considerably higher. Besides CML, Philadelphia chromosome-negative myeloproliferative neoplasms (MPN, polycythaemia vera [PV], essential thrombocythaemia [ET], primary myelofibrosis [MF]) are associated with thrombotic events occurring frequently at unusual sites (portal and splenic veins, mesenteric arteries, cerebral sinuses).…”
Section: Discussionmentioning
confidence: 99%